1991
DOI: 10.1002/anie.199100171
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Molecular Stacking of Anthocyanins—Flower Color Variation

Abstract: In 1913 Willstatter made the striking observation that the same pigment can give rise to different colors. Thus, the same pigment, cyanin, is found in the blue cornflower and in the red rose. Willstatter attributed the variety of flower colors to different pH values in solution. Indeed, anthocyanin changes its color with pH; it appears red in acidic, violet in neutral, and blue in basic aqueous solution. Willsfutter's pH-theory for explaining flower color variation is still to be found in major text books of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
311
0
8

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 460 publications
(326 citation statements)
references
References 107 publications
7
311
0
8
Order By: Relevance
“…Among them, flavones are found extensively in land plants but are absent in almost all members of the Cruciferae (Martens and Mithöfer, 2005;Zhou and Ibrahim, 2010). In plants, flavones play important physiological roles, including UV protection (Schmitz-Hoerner and Weissenböck, 2003), interactions with other organisms (Peters et al, 1986;Kong et al, 2007), regulation of auxin transport (Mathesius et al, 1998), and copigmentation in flowers (Goto and Kondo, 1991). On the other hand, flavones as dietary constituents or supplements have become increasingly popular due to their health-beneficial effects, such as cancer prevention (Bontempo et al, 2007;Cai et al, 2007;Liu et al, 2007), antioxidation (Park et al, 2007), antiviral activities (Yarmolinsky et al, 2012), reduction of risks of cardiovascular diseases (Baek et al, 2009), and suppression of cholesterol levels (Dharmarajan and Arumugam, 2012).…”
mentioning
confidence: 99%
“…Among them, flavones are found extensively in land plants but are absent in almost all members of the Cruciferae (Martens and Mithöfer, 2005;Zhou and Ibrahim, 2010). In plants, flavones play important physiological roles, including UV protection (Schmitz-Hoerner and Weissenböck, 2003), interactions with other organisms (Peters et al, 1986;Kong et al, 2007), regulation of auxin transport (Mathesius et al, 1998), and copigmentation in flowers (Goto and Kondo, 1991). On the other hand, flavones as dietary constituents or supplements have become increasingly popular due to their health-beneficial effects, such as cancer prevention (Bontempo et al, 2007;Cai et al, 2007;Liu et al, 2007), antioxidation (Park et al, 2007), antiviral activities (Yarmolinsky et al, 2012), reduction of risks of cardiovascular diseases (Baek et al, 2009), and suppression of cholesterol levels (Dharmarajan and Arumugam, 2012).…”
mentioning
confidence: 99%
“…A homologous series with one to three hydroxyl groups on the B-ring evolves. The introduction of the hydroxyl groups also leads to the presence of adjacent hydroxyl groups in cyanidin chloride and delphinidin chloride, which is an essential condition for their ability to form chelate-complexes [15][16][17][18]. Increasing number of hydroxyl groups and the presence of adjacent hydroxyl groups should also stabilize the formation of PLA-dye complexes [19].…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanins are susceptible to alteration of colour due to inter alia pH, metal ions, processing temperature (Timberlake 1981 ;Brouillard 1988), sucrose concentration , ascorbic acid (Poei-Langston & Wrolstad 1981), endogenous polyphenoloxidase (WescheEbeling & Montgomery 1990), and commercial pectinase treatment (Jiang et al 1990). However, Goto & Kondo (1991) suggested that the unexpected stability of anthocyanins in vivo could be the result of metal complexation, self-association, copigmentation, or molecular stacking. All four types of stabilisation have been demonstrated recently (Kondo et al 1992) in commelinin, a blue anthocyanin.…”
Section: Received 26 April 1993; Accepted 4 August 1993mentioning
confidence: 99%